Investigation of Material and Structural Effects on MEMS Thermal Sensor Characteristic - Mohd Hafiz Ismail; Bibi Nadia Taib; Shazlina Johari; Hasnizah Aris; Linda Silvia, (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
In this paper, the design, simulation, and analysis of a MEMS-based thermal sensor are presented using MEMSPro and ANSYS. The study aims to assess the effect of significant design parameters on the sensor’s performance. The sensor was virtually fabricated in MEMSPro using standard microfabrication processes, including photolithography, deposition, and etching. ANSYS software was used to conduct finite element analysis in order to observe the sensor’s thermal response under varying conditions. Four primary parameters were investigated: coil materials (brass, gold, and copper), coil thicknesses (1 µm, 3 µm, and 6 µm), parylene types (Parylene-C, -F, and -N), and input temperatures ranging from 10 °C to 90 °C. The results demonstrate that these parameters significantly influence the average temperature and electrical resistance across the sensor. Brass exhibited the highest average temperature, while Parylene-N, with the highest thermal conductivity, produced the greatest thermal response. These findings provide insights into optimizing MEMS thermal sensor designs for enhanced sensitivity and stability, with potential applicability in real-time temperature monitoring systems.